(untitled) (Iraqi Journal of Medical Sciences, 2017)
Cervical cancer (CC) represents the most common cancer among women in developing countries. Present confirmation suggests that human papillomavirus (HPV) testing is more efficient than cytology for CC screening. Even if implementing a high-quality cytology programme in these countries is probable, it would only be fairly effective. This is because the presently used Pap test misses approximately 50% of high-grade precursor lesions and cancers with a single screening. Several screening alternatives have been planned for areas with incomplete resources. Amid these, visual inspection with acetic acid (VIA) includes the application to the cervix of 5% diluted acetic acid (vinegar), making the dysplastic epithelium turn white (acetowhitening). Screening with HPV testing and VIA have been verified to be effective and potentially cost-effective in low-resource settings, allowing for fewer follow-up visits (e.g., screen-and-treat approaches) and, in the case of HPV testing, automated processing of laboratory specimens that reduces resource and quality control necessities Keywords:Cervical cancer, screening, cytology, human papillomavirus testing, visual inspection with acetic acid Citation: Ban J. Qasim. Cervical cancer screening in developing countries. Iraqi JMS. 2017; Vol. 15(1): 1-3. doi: 10.22578/IJMS.15.1.1